2014
DOI: 10.3892/or.2014.3144
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB signaling modulates radiation-induced microglial activation

Abstract: Microglial activation has been suggested to be associated with the incidence of radiation-induced brain injury. The present study investigated the molecular mechanism(s) involved in radiation-induced activation of the microglia. Mouse microglial BV-2 cells were exposed to different doses of radiation. The release of inflammatory factors was evaluated by enzyme-linked immunosorbent assay and real-time reverse transcriptase polymerase chain reaction. Protein expression was determined by immunocytochemistry and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Radiation-induced brain injury (RIBI) remains a common and severe side effect, and approximately 50% of all survivors may develop lateonset radiation-induced injury of normal brain tissues [1,[4][5][6][7] , which includes the progressive impairment of cognitive functions. Many pre-clinical studies have demonstrated that inflammatory responses tend to occur after CRT and may contribute to RIBI [8][9][10] , which suggests that neuro-inflammation is implicated in RIBI [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation-induced brain injury (RIBI) remains a common and severe side effect, and approximately 50% of all survivors may develop lateonset radiation-induced injury of normal brain tissues [1,[4][5][6][7] , which includes the progressive impairment of cognitive functions. Many pre-clinical studies have demonstrated that inflammatory responses tend to occur after CRT and may contribute to RIBI [8][9][10] , which suggests that neuro-inflammation is implicated in RIBI [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that irradiation-induced microglial activation may play an important part in RIBI. In vitro studies have shown that irradiation could induce microglial activation, which, in turn, led to elevated expression of a variety of proinflammatory genes, including IL-1β, IL-6, TNF-α, and COX-2 [11] .…”
Section: Introductionmentioning
confidence: 99%
“…5 a). In addition, previous studies proved that the inflammatory state of microglia after IR activation was related to distinct signaling pathways, such as the NF-κB and MAPK pathways [ 26 , 27 ]. Therefore, selective pharmacological inhibitors of the NF-κB pathway (Bay-11-7082) and the three main branches of MAPK pathway, including SP600125 (c-Jun N-terminal kinase, JNK), U0126 (extracellular signal-regulated kinase, ERK), and SB203580 (p38) were used to detect the possible pathways that act on the expression of the two selected RILs.…”
Section: Resultsmentioning
confidence: 99%
“…MG132 inhibits NF-κB activation by irradiation. NF-κB is a crucial transcription factor that regulates the expression of genes linked to apoptosis, survival, proliferation, invasion, metastasis and tumor cell transformation (17,18). NF-κB has been extensively reported to be implicated in cancer cell radiosensitivity due to their role of transcriptional regulation upon radiation exposure.…”
Section: Mg132 Increased the Dicentric Chromosome Ratio Treated By Irmentioning
confidence: 99%